Experimental study of antiangiogenic and photodynamic therapies combination for treatment of peritoneal carcinomatosis: preliminary results - Piatrouskaya, N.A.; Kharuzhyk, S.A.; Vozmitel, M.A.; Mazurenko, A.N.; Istomin, Y.P. (Experimental Oncology, 2010)
Aim: To create adequate orthotopic model of peritoneal carcinomatosis in rats using a transplantable rat tumor M-1 sarcoma, to assess the early tumor response after intraperitoneal photodynamic and/or antiangiogenic therapy for peritoneal carcinomatosis. Methods: In 14–18 days after intraperitoneal inoculation, eighteen tumor-bearing animals were divided into three groups and undergone intraperitoneal photodynamic therapy and/or antiangiogenic therapy. Assessment of the tumor posttreatment changes was performed using a method of vital staining with Evans blue, MRI-monitoring and morphologic investigation. Results: Percentage of necrosis in disseminated tumors of animals undergone combination therapy significantly higher then after each of the methods alone and achieved 89.46% vs 41.47% after antiangiogenic therapy and 69.73% after photodynamic therapy. Contrast-enhanced MRI showed entirely necrotic tumor nodes in rats undergone the combination therapy. Morphologic study confirmed that tumor response after combination therapy was characterized by maximal spread of necrotic and inflammatory changes in tumor. Conclusion: Preliminary results demonstrate enhance of the treatment outcome after combination of antiangiogenic and intraperitoneal photodynamic therapies for peritoneal carcinomatosis in rats.